Treatment of macular diseases: an overview of key randomized clinical trials - E. V. Bobykin; O. V. Morozova; N. S. Beresneva (Российский офтальмологический журнал)
Macular diseases are traditionally a serious issue in ophthalmology, which has great social impact due to widespread occurrence and significant vision loss, often irreversible. Over the past few decades, the possibilities for the diagnosis and treatment of pathologies of the retina and choroid have been significantly expanded. Randomized clinical trials provided ophthalmologists with valuable information on the natural course and treatment strategies of common retinal diseases from the viewpoint of evidence-based medicine. However, due to the large number of trials conducted, it is often difficult to make an adequate choice of data to be used in daily practice. In this review, we systematize the most valuable randomized clinical trials. To this end, we selected 42 randomized clinical studies conducted between 1979 and 2019 and focused on the treatment of age-related macular degeneration (AREDS 1, AREDS 2, ANCHOR, MARINA, PrONTO, CATT, IVAN, VIEW 1, VIEW 2, EVEREST II, PLANET, SEVEN-UP, ALTAIR, HAWK, HARRIER), choroidal neovascularization of multiple etiology (myopic, post-inflammatory, angioid-streak-related, etc. — RADIANCE, REPAIR, MYRROR, MINERVA), diabetic eye lesions (diabetic retinopathy and diabetic macular edema — ETDRS, DRCR.net Protocols B, I, S and T, RISE, RIDE, VIVID-DME, VISTA-DME, MEAD, FAME), retinal vein occlusions (BVOS, CVOS, SCORE-CRVO, SCORE-BRVO, BRAVO, CRUISE, GALILEO, COPERNICUS, VIBRANT), as well as retinopathy of prematurity (CRYO-ROP, ETROP, RAINBOW). The review summarizes the main results of these studies, which confirm the effectiveness and safety of such treatment methods as antiVEGF and photodynamic therapy, retinal laser photocoagulation, cryotherapy, corticosteroids and nutraceuticals from the viewpoint of evidence-based medicine. For greater clarity, we provide a table summarizing information on each of the randomized clinical trials considered.